فعالية البرنامج القومي لتطوير الريف المصري في تحقيق الحماية الاجتماعية المستدامة للمجتمعات المستهدفة - بليح، مخلص رمضان محمد أحمد (الجمعية المصرية للأخصائيين الإجتماعيين, 2022)
تمثلت مشكلة الدراسة الحالية في تحديد فعالية البرنامج القومي لتطوير الريف المصري في تحقيق الحماية الاجتماعية المستدامة للمجتمعات المستهدفة. وكانت أهداف الدراسة كالتالي: ١- تحديد مستوى برامج الحماية الاجتماعية للمجتمعات المستهدفة. ٢- قياس مستوى فعالية البرنامج القومي لتطوير الريف المصري في تحقيق الحماية الاجتماعية المستدامة للمجتمعات المستهدفة. ٣- تحديد الصعوبات التي تواجه فعالية البرنامج القومي لتطوير الريف المصري في تحقيق الحماية الاجتماعية المستدامة للمجتمعات المستهدفة. ٤- تحديد مقترحات زيادة فعالية البرنامج القومي لتطوير الريف المصري في تحقيق الحماية الاجتماعية المستدامة للمجتمعات المستهدفة. 5- التوصل إلى تصور تخطيطي مقترح لزيادة فعالية البرنامج القومي لتطوير الريف المصري في تحقيق الحماية الاجتماعية المستدامة للمجتمعات المستهدفة. وكانت فروض الدراسة كالتالي: ١- من المتوقع أن يكون مستوى برامج الحماية الاجتماعية للمجتمعات المستهدفة متوسطاً. ٢- من المتوقع أن يكون مستوى فعالية البرنامج القومي لتطوير الريف المصري في تحقيق الحماية الاجتماعية المستدامة للمجتمعات المستهدفة متوسطاً. ٣- توجد علاقة دالة إحصائيا بين بعض المتغيرات الديموجرافية للمستفيدين وتحديدهم لمستوى برامج الحماية الاجتماعية للمجتمعات المستهدفة. ٤- توجد علاقة دالة إحصائياً بين بعض المتغيرات الديموجرافية للمستفيدين وتحديدهم لمستوى فعالية البرنامج القومي لتطوير الريف المصري في تحقيق الحماية الاجتماعية المستدامة للمجتمعات المستهدفة والدراسة من نوع الدراسات التقييمية وتم استخدام منهج المسح الاجتماعي وتم جمع البيانات بواسطة استمارة استبار من عينة عمدية من المستفيدين من برامج الحماية الاجتماعية المستدامة حجمها ٢٠٤. ومن أهم نتائج الدراسة: ١- الإجابة عن جميع تساؤلات الدراسة. ٢- صدق الفرض الأول. ٣- صدق الفرض الثاني. ٤- صدق الفرض الثالث جزئيا. 5- صدق الفرض الرابع جزئيا. ٦- تقديم تصور تخطيطي مقترح لزيادة فعالية البرنامج القومي لتطوير الريف المصري في تحقيق الحماية الاجتماعية المستدامة للمجتمعات المستهدفة. The problem of the current study was to determine the effectiveness of the national program for the development of the Egyptian countryside in achieving sustainable social protection for the target communities. The aims of the study were as follows: 1- Determining the level of social protection programs for the targeted communities. 2- Measuring the effectiveness of the national program for the development of the Egyptian countryside in achieving sustainable social protection for the targeted communities. 3- Identifying the difficulties facing the effectiveness of the national program for the development of the Egyptian countryside in achieving sustainable social protection for the target communities. 4- Determining proposals to increase the effectiveness of the national program for the development of the Egyptian countryside in achieving sustainable social protection for the target communities. 5- Reaching a proposed planning vision to increase the effectiveness of the national program for the development of the Egyptian countryside in achieving sustainable social protection for the targeted communities. The study hypotheses were as follows: 1- It was expected that the level of social protection programs for the targeted communities will be medium. 2- It was expected that the level of effectiveness of the national program for the development of the Egyptian countryside in achieving sustainable social protection for the targeted communities will be medium. 3- There was a statistically significant relationship between some demographic variables of the beneficiaries and their determination of the level of social protection programs for the targeted communities. 4- There was a statistically significant relationship between some demographic variables of the beneficiaries and their determination of the level of effectiveness of the National Program for the Development of the Egyptian Rural in achieving sustainable social protection for the target communities. The study was of the type of assessment studies, and the social survey method was used, and the data was collected by a questionnaire form from a non-random sample of 204 beneficiaries of sustainable social protection programs. Among the most important results of the study: 1- Answering all the questions of the study. 2- The validity of the first hypothesis. 3- The validity of the second hypothesis. 4- The third hypothesis is partially valid. 5- The fourth hypothesis is partially valid. 6- Presenting a proposed planning vision to increase the effectiveness of the national program for the development of the Egyptian countryside in achieving sustainable social protection for the target communities.
Keywords: الخدمة الاجتماعية -- الحماية الاجتماعية -- التنمية المستدامة -- التنمية الريفية -- الريف المصري